Social determinants of health and cancer mortality in the Reasons for Geographic and Racial Differences in Stroke (REGARDS) cohort study. Issue 1 (3rd September 2021) - Pinheiro, Laura C.; Reshetnyak, Evgeniya; Akinyemiju, Tomi; Phillips, Erica; Safford, Monika M.
Abstract : Background: Social determinants of health (SDOHs) cluster together and can have deleterious impacts on health outcomes. Individually, SDOHs increase the risk of cancer mortality, but their cumulative burden is not well understood. The authors sought to determine the combined effect of SDOH on cancer mortality. Methods: Using the Reasons for Geographic and Racial Differences in Stroke (REGARDS) cohort, the authors studied 29, 766 participants aged 45+ years and followed them 10+ years. Eight potential SDOHs were considered, and retained SDOHs that were associated with cancer mortality ( P < .10) were retained to create a count (0, 1, 2, 3+). Cox proportional hazard models estimated associations between the SDOH count and cancer mortality through December 31, 2017, adjusting for confounders. Models were age‐stratified (45‐64 vs 65+ years). Results: Participants were followed for a median of 10.6 years (interquartile range [IQR], 6.5, 12.7 years). Low education, low income, zip code poverty, poor public health infrastructure, lack of health insurance, and social isolation were significantly associated with cancer mortality. In adjusted models, among those <65 years, compared to no SDOHs, having 1 SDOH (adjusted hazard ratio [aHR], 1.39; 95% CI, 1.11‐1.75), 2 SDOHs (aHR, 1.61; 95% CI, 1.26‐2.07), and 3+ SDOHs (aHR, 2.09; 95% CI, 1.58‐2.75) were associated with cancer mortality ( P for trend <.0001). Among individuals 65+ years, compared to no SDOH, having 1 SDOH (aHR, 1.16; 95% CI, 1.00‐1.35) and 3+ SDOHs (aHR, 1.26; 95% CI, 1.04‐1.52) was associated with cancer mortality ( P for trend = .032). Conclusions: A greater number of SDOHs were significantly associated with an increased risk of cancer mortality, which persisted after adjustment for confounders. Abstract : Individually, social determinants of health increase the risk of cancer mortality, but their cumulative burden is not well understood. A greater number of social determinants of health in the same individual are found to be significantly associated with an increased risk of cancer mortality, even after adjustment for a variety of confounders.